Narrating the Holocaust through museums: the cases of Guatemala and Argentina - Wechsler, Wanda (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
The turn of the century saw the proliferation of museums dedicated to the memory and history of the Holocaust in Latin America. These museums were built as spaces dedicated to reflect and transmit the history of the Jewish Holocaust in countries where the materiality of the events did not take place. In each country, the museums have elaborated diverse relationships with the recent past. In this way, a memory considered global interacted in different ways with local memories. This article investigates the creation, history and samples of origin of the Holocaust Museum located in Guatemala City and the museum of Buenos Aires. Each museum was built in relation to their recent pasts and it is the interest of this paper to describe and reflect on the uses of memories and the particularities of each country through museum exhibits. This case of Guatemala has the particularity of being the only Latin American country that contains in its recent history a genocide recognized by the UN. It is the interaction between the memory of the Guatemalan genocide and the Jewish genocide that we seek to illuminate. In the case of Argentina, it is a country with an enormous history linked to human rights and the memory of state terrorism. In what ways do memories interact, can they illuminate or obstruct each other?